(untitled) (Nóema, 2023)
The text consists of the reworked transcript of a dialogue that the independent research group "Inoperoso", held with Roberto Esposito on 11 May 2023. The theme of the discussion was the questioning of a possible critical topicality of the ontological political perspective that Esposito himself first described as "impolitic thought" and then, in more recent texts, as "destituting thought". In claiming such a topicality, the members of "Inoperoso" were confronted with the subsequent development of Esposito’s thought, and in particular with the criticism of the contradictions of the destituting perspective that he put forward in his recent trilogy dedicated to the proposal of the "instituting paradigm". The ultimate intention of the dialogue was to develop a philosophical practice focused not on issues within the narrow consideration of a single author or specific theme, but rather aimed at a collective exercise of reflection on the great questions and issues that affect every human being, looking on the one hand at the forms in which the current institutional conjuncture tends to inhibit such an exercise, and on the other at the opportunities for transformation that it can concretely offer.